Teachers' beliefs and practices about oral corrective feedback in university EFL classes. (6th March 2021) - Yüksel, Doğan; Soruç, Adem; McKinley, Jim
Abstract: This study examined (in)congruences between beliefs and practices of EFL university teachers on in‐class oral corrective feedback (OCF). The participants were 20 university English language teachers from a private university in Turkey. Data were collected via video‐recorded non‐participant detached observation, a task about OCF to determine the beliefs of the teachers, and a stimulated recall interview. The results showed incongruence between what the teachers said they believed and what they did. However, teachers' beliefs and practices were similar regarding whether the errors should be corrected, when errors should be corrected, and who should correct them. Particularly notable in this study was the finding that those teachers with the greatest incongruence almost always stood by their decisions, even after they watched their unsuccessful OCF practices. Resumen: Bu çalışma, üniversitede İngilizceyi yabancı dil olarak öğreten okutmanların sınıf içi sözlü düzeltici dönüt (SDD) konusundaki inançları ve uygulamaları arasındaki uyum(suzluğ)u incelemiştir. Katılımcılar, Türkiye'deki bir vakıf üniversitesinde çalışan 20 okutmandır. Veriler videoya kaydedilmiş bağımsız gözlem, okutmanların SDD ile ilgili inançlarını belirlemek için tasarlanmış bir etkinlik ve çağrışım tekniğine dayalı görüşme yoluyla toplanmıştır. Sonuçlar, okutmanların inandıklarını söyledikleri ile yaptıkları arasında tutarsızlıklar olduğunu göstermiştir. Ancak, hataların düzeltilmesi gerekip gerekmediği, hataların ne zaman düzeltilmesi gerektiği ve kimin düzeltmesi gerektiği konusunda öğretmenlerin inançları ve uygulamaları benzerlik göstermiştir. Bu çalışmada özellikle dikkat çekici olan, en büyük uyumsuzluğa sahip okutmanların, başarısız SDD uygulamalarını izledikten sonra bile uygulamalarını değiştirmek istememeleri ve verdikleri kararlarında ısrarcı olamalarıdır.